Peer-to-peer kilowatt and negawatt trading: A review of challenges and recent advances in distribution networks. (November 2022) - Azim, M. Imran; Tushar, Wayes; Saha, Tapan K.; Yuen, Chau; Smith, David
Abstract: Peer-to-peer trading is a potential future-generation energy management mechanism that enables prosumers — electricity consumers who can generate and control their energy — to earn monetary gains. However, the physical deployment of this trading technique in distribution networks — to accommodate prosumers — poses some technical challenges. To address these challenges, this paper presents an up-to-date literature review in regard to the reliable application of peer-to-peer kilowatt and negawatt trading in distribution networks. An overview, of trading types; communication systems and issues; market structures and setup; and physical network of peer-to-peer trading, is provided. For a comprehensive review of the impact of peer-to-peer trading on actual distribution networks, firstly, the key elements of such physical networks are discussed. Then, the fundamental challenges identified in existing literature, on peer-to-peer kilowatt and negawatt trading in distribution networks, are introduced. Further, technical approaches undertaken by recent studies to address the identified challenges within peer-to-peer trading, are described extensively. The article is concluded with some directions for future research into peer-to-peer trading in distribution networks. Highlights: Detailed background discussion of peer-to-peer trading at the distribution level. The introduction of key elements of distribution networks for peer-to-peer trading. The identification of fundamental challenges to accommodate peer-to-peer trading. The demonstration of core techniques to address the identified challenges. Directions for future research into peer-to-peer trading in distribution networks.